OrCam MyEye 2.0, A Dire Need to Revolutionize the Lives of Congenital or Acquired visually Impaired Patients in Pakistan.: Doi: 10.36351/pjo.v40i2.1679 - Sajjad, Waseem; Wajahat Ullah Ismail (Pakistan Journal of Ophthalmology, 2024)
I am writing to highlight the pressing issues in the management of congenital or acquired visually impaired patients, and to accentuate the dire need for an alternative approach and attitude towards their rehabilitation in Pakistan. To lessen the socio-emotional impacts and dependency of patients who are blind or visually impaired, as well as to improve their quality of life, ophthalmologists must pay close attention to the inadequate use of AI visual assistance systems and contemporary technology.1